Shahzin Enterprise / Siti Aliah Ali, Nurul Anisah Abdul Rahim, Umi Hana Umairah Ayub Zambri and Nur Aisya Nazri - Ali, Siti Aliah; Abdul Rahim, Nurul Anisah; Ayub Zambri, Umi Hana Umairah; Nazri, Nur Aisya (2019)
A bakery is an establishment that produces and sells four-based food baked in an oven such as bread, cookies, cakes, pastries, and pies. Some retail bakeries are also cafes, serving coffee and tea to customers who wish to consume the baked goods on the premises.